Aplikasi Administrasi Keanggotaan Fitness Center “X” Berbasis Website dan Mobile Device - Stevanus Michael Sugiarto; Henry Palit; Ibnu Gunawan (Jurnal Infra, 2016)
Technology is developing very rapidly create business processes that run with the conventional system began to be abandoned by the businesses. Technology makes business processes run more efficiently, quickly, accurately, and reduce the chances of problems by human error. This system is aimed at one of the business people in the fitness field. The system built is believed will make business processes better, as well as businesses can monitor his business handled from anywhere and anytime.Based on the experimental testing of the system, the system has been able to run as desired fitness businesses. The system that has been integrated between the systems with each other to make businesses can monitor and run its business processes better. The data has been computerized data that makes the data easier to back up, so the possibility of data loss can be minimized.